Websites and CSR Disclosure: An Exploratory Study of Corporate Behemoths in India - Sharma, Shadhana (IJRDO-Journal of Applied Science, 2020)
Corporate houses in India adopted digital communication for the purpose of legitimising their action much late. With the imposition of GRI, it became a compulsive practice to disclose CSR activities on the website. The compulsion also prompted them to sometimes start experimenting with different forms of social media in addition website for a purposeful communication. Digital media has virtually made other conventional forms of communication obsolete for the PR professionals. The extensive use of digital communication is not only a cheaper mode of communication but it also increases the faith of stakeholders in terms of knowledge about the company as the information is readily available in the website. In an era of brand perception war and optics based discourse, websites have become an inseparable part of building trust. Corporate social responsibility is no more a philanthropic activity buy now it is an in-built corporate strategy. The most effective mechanism for any strategy to succeed requires a certain amount of faith of the beneficiaries and stakeholders in the intention and activities of the investor. A fair level of disclosure and easy accessibility to the disclosed information helps the company to win loyal brand followers and it serves as most effective advertising strategy. The paper explores the how far Indian corporate giants are interested to use website for the purpose of disclosure of CSR communication through the websites to win legitimacy for their actions.